School Peer Non-academic Skills and Academic Performance in High School - Palardy, Gregory J. (Frontiers in Education, 2019)
Research shows that students’ non-academic attributes, such as forms of engagement, dispositions, and social and emotional skills, are associated with a range of outcomes including academic performance. However, little research has investigated the effects of school peer non-academic attributes on academic performance. This study begins to address this gap in the research literature by examining the effects of ten measures of school peer nonacademic attributes. Importantly, most of the non-academic attributes examined in this study are malleable through school-based interventions. The results show that five measures of school peer attributes have medium to large effects on academic performance including collaboration skills (a social-emotional characteristic), conscientiousness and belonging (dispositions), and cognitive and behavioral engagement. In contrast, the corresponding effects of student’s own non-academic attributes were uniformly smaller. These findings indicate that the non-academic attributes of one’s school peers play an important role in academic performance above and beyond one’s own non-academic attributes. These results suggest that school-wide interventions and instructional practices designed to improve the non-academic skills of all students will provide additional benefits compared with interventions focusing on students with the most under-developed non-academic attributes.